1999
DOI: 10.2307/2641349
|View full text |Cite
|
Sign up to set email alerts
|

Low Acute Exposure to Organophosphate Produces Long-Term Changes in Bird Feeding Behavior

Abstract: Although organophosphates and carbamates are the most widely applied insecticides and are associated with mass killing of birds, little is known of their sublethal effects. One well-known result of sublethal exposure to toxin, conditioned taste aversion, was tested in a series of field experiments in which independent replicates were large numbers of breeding territories of Red-winged Blackbirds (Agelaius phoeniceus). While birds freely consumed untreated insect prey offered to them in control territories, tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…A few notable exceptions have demonstrated the utility of studying detailed behavioural responses among individually known, free‐ranging animals in determining the effect of a repellent (e.g. racoons Procyon lotor , Nicolaus, Hoffman & Gustavson 1982; Semel & Nicolaus 1992; red‐winged blackbirds Agelaius phoenicus , Nicolaus & Lee 1999; black bears Ursus americanus , Ternent & Garshelis 1999). Our work adds a further level of detail to the study of behaviour aversion (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A few notable exceptions have demonstrated the utility of studying detailed behavioural responses among individually known, free‐ranging animals in determining the effect of a repellent (e.g. racoons Procyon lotor , Nicolaus, Hoffman & Gustavson 1982; Semel & Nicolaus 1992; red‐winged blackbirds Agelaius phoenicus , Nicolaus & Lee 1999; black bears Ursus americanus , Ternent & Garshelis 1999). Our work adds a further level of detail to the study of behaviour aversion (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Another observed long-term effect regards changes in feeding behaviour produced by organophosphates (i.e., parathion). This can occur at levels below those inducing outward illness or even those that depress brain AChE activity, possibly via a mechanism of conditioned food aversion related to sublethal toxicity (Nicolaus and Lee, 1999).…”
Section: Risk Assessment Of Topical Antiparasitic Exposure In Avian Smentioning
confidence: 99%
“…Data from the video recordings (Trial 5) of mixed groups of geese from shared previous exposure to endophyte showed that previous exposure can influence subsequent feeding r esponse (Table 2). Learned geese were slower to start feeding and spent less time feeding, suggesting that the birds had developed through PDF a CTA described in Nicolaus & Lee (1999).…”
Section: Learned Response With Seed Feedingmentioning
confidence: 99%
“…), in the form of "naïve" geese feeding within sight of the learned groups, should have stimulated the learned geese to accept the food. PDF may be one mechanism which provokes the "learned" geese to recognise and reject the E+ but it is possib le that a f orm of CTA (Garcia et al 1974;Riley & Tuck 1985;Nicolaus & Lee 1999) could influence how the geese recognised and so avoided the E+ material. Our work is in agreement with the results of Conover & Messmer (1996b) but our work is the first to identify specific endophyte alkaloids involved in bird responses.…”
Section: Figurementioning
confidence: 99%